Playing for pizza - Grisham, John, ....- (London : Arrow, 2008)
With a 17-point lead and just minutes to go, Rick Dockery provided what was arguably the worst single performance in the history of the NFL. Overnight, he became a national laughing stock and, of course, was immediately dropped by the Browns and shunned by all other teams. But all Rick knows is football, and he insists that his agent, Arnie, finds a team that needs him. Against enormous odds, Arnie finally locates just such a team and informs Rick that, miraculously, he can in fact now be a starting quarterback - for the mighty Panthers of Parma, Italy. Rick reluctantly agrees to play for them - at least until a better offer comes along - and heads off to Italy. He knows nothing about Parma (not even where it is), has never been to Europe, and doesn't speak or understand a word of Italian. The land of opera, fine wines, extremely small cars, romance and football americano certainly holds a few surprises for Rick Dockery.
Keywords: Fiction